1996
DOI: 10.1677/joe.0.1480531
|View full text |Cite
|
Sign up to set email alerts
|

Expression of α2- and β-adrenoceptor subtypes in human islets of Langerhans

Abstract: Sequences from cDNA molecules encoding alpha 2-adrenoceptor subtype genes were subcloned into prokaryotic vectors and riboprobes generated to hybridise selectively with each of the human alpha 2C2-, alpha 2C4- and alpha 2C10-adrenoceptor subtype mRNA species. The riboprobes were labelled with either 32P or digoxigenin and used to study the expression of alpha 2-adrenoceptor subtypes in sections of human pancreas, in isolated human islets of Langerhans and in clonal HIT-T15 pancreatic beta-cells. Using a ribonu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 0 publications
2
20
1
Order By: Relevance
“…39 and our unpublished observations), but whether local synthesis, storage, and release can indeed increase local T1AM concentration remains to be determined. TAAR1 and ADRA2A are expressed in human islets (Supplemental Figure 6) (40), and regardless of whether T1AM is a physiological stimulator of insulin release via Taar1 or an inhibitor of insulin release via Adra2a, our results support the notion that pharmacological agonism of Taar1 and/or antagonism of Adra2a might be explored to augment insulin secretion for therapeutic purposes.…”
Section: Figuresupporting
confidence: 73%
“…39 and our unpublished observations), but whether local synthesis, storage, and release can indeed increase local T1AM concentration remains to be determined. TAAR1 and ADRA2A are expressed in human islets (Supplemental Figure 6) (40), and regardless of whether T1AM is a physiological stimulator of insulin release via Taar1 or an inhibitor of insulin release via Adra2a, our results support the notion that pharmacological agonism of Taar1 and/or antagonism of Adra2a might be explored to augment insulin secretion for therapeutic purposes.…”
Section: Figuresupporting
confidence: 73%
“…Conversely, P and T diminished insulin secretion by 40-49% and 51-45%, respectively, with the doses currently employed. As shown by other authors, the uneven effect of adrenergic antagonists could be ascribed to the relative abundance or activity of α 2 -adrenoceptors in B-cells, as compared with α 1 -and β 2 -adrenoceptors [5][6][7][8]. On the other hand, Schuit et al showed that P was ineffective in both a and B-cells [31]; such discrepancy with our results can be attributed to the method used in each case.…”
Section: Figurecontrasting
confidence: 70%
“…Catecholamines (CAs) contribute to this mechanism by exerting a direct and dual effect on the B-cell to induce either inhibition or stimulation of insulin secretion through their interaction with α 2 or α 1 and β 2 adrenergic receptors, respectively [3,4]. Since islet B-cells have more α 2 than α 1 and β 2 adrenergic receptors, physiological concentrations of CAs will bind mainly to the α 2 population receptors and thus inhibit insulin secretion [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, norepinephrine (NE) released by sympathetic terminals stimulates beta-cell α2 adrenergic receptors that acting through G i or G 0 proThe role played by neural inputs on beta-cell function has been a matter of intense investigation over the latest forty years [1]. The highest effect is believed to be exerted by parasympathetic fibres originated at the teins negatively modulate adenyl cyclase activity, reducing cAMP production and, ultimately, insulin secretion [7,8,9].…”
Section: :1522-1531]mentioning
confidence: 99%